2017
DOI: 10.1186/s12888-017-1477-x
|View full text |Cite
|
Sign up to set email alerts
|

Case report of anti-N-methyl-D-aspartate receptor encephalitis in a middle-aged woman with a long history of major depressive disorder

Abstract: BackgroundAnti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune disease involving antibodies against the NR1 subunits of NMDARs. The disease shows variable clinical presentation, and involves new-onset acute psychotic symptoms, making it difficult to differentiate from major depressive disorder with psychotic symptoms. Potential associations between this autoimmune disorder and onset or progression of major depressive disorder remains unclear.Case presentationWe present a rare case of a pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
3
1
1
Order By: Relevance
“…Here we present the third published case of anti-NMDA receptor encephalitis, which resembles a major depression without any initial neurological signs or symptoms. In contrast to the other two cases, a 16-year-old girl ( 15 ) and a 52-year-old woman ( 16 ), our patient did not show any distinct concomitant psychotic symptoms, other than some attenuated positive symptoms and basic symptoms according to a sensitive early recognition scale for psychosis, ERIraos. Although the clinical presentation was dominated by core symptoms of depression and familiar features like preceding psychosocial stress factors (break up of a relation, graduation year), there were also some apparent atypical aspects.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Here we present the third published case of anti-NMDA receptor encephalitis, which resembles a major depression without any initial neurological signs or symptoms. In contrast to the other two cases, a 16-year-old girl ( 15 ) and a 52-year-old woman ( 16 ), our patient did not show any distinct concomitant psychotic symptoms, other than some attenuated positive symptoms and basic symptoms according to a sensitive early recognition scale for psychosis, ERIraos. Although the clinical presentation was dominated by core symptoms of depression and familiar features like preceding psychosocial stress factors (break up of a relation, graduation year), there were also some apparent atypical aspects.…”
Section: Discussioncontrasting
confidence: 93%
“…Notably, the psychopathology of those cases is dominated by psychotic, cognitive, and catatonic symptoms (12)(13)(14). To our knowledge, there are only two case reports in the literature of anti-NMDAR encephalitis, which mimic a major depressive episode with psychotic symptoms (15,16). Here we report the first case of a patient with anti-NMDAR encephalitis, which presents as a major depressive episode without distinct psychotic symptoms like delusion, hallucination, or catatonia, as well as without any neurological signs or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Anti NMDA receptor encephalitis is autoimmune disorder first described by Dalmau and colleagues in 2007 among 12 women as paraneoplastic condition. 2 It is a rare disorder with very low incidence and the prevalence in children is exactly unknown. Remy KE et al reported more than 600 cases including paediatric ones and Goldberg EM reported 577 cases with 37% children.…”
Section: Discussionmentioning
confidence: 99%
“…Anti N-Methyl-D-Aspartate Receptor (NMDAR) encephalitis is a synaptic autoimmune condition. 1,2 It is considered second commonest cause of autoimmune encephalitis after acute disseminated e n c e p h a l o m y e l i t i s a m o n g c h i l d r e n a n d adolescents. 1 It is more common among females during adolescence and among males in children younger than 12 years.…”
Section: Introductionmentioning
confidence: 99%
“…Los receptores NMDA tienen una clara relación fisiopatológica y terapéutica con la depresión. Así, la encefalitis provocada por anticuerpos anti R-NMDA se caracteriza por un trastorno depresivo mayor [95]. Además, en estudios postmortem de pacientes deprimidos, se ha podido detectar un aumento significativo de la subunidad NR2C de R-NMDA en el locus coeruleus [88] y una reducción de las subunidades NR2A (54%) y NR2B (48%) del receptor NMDA en corteza prefrontal [84], junto a un aumento de la subunidad NR2A en la amígdala de los sujetos deprimidos vs. controles [96].…”
Section: Disfunción a Nivel De Receptores Glutamatérgicos Ionotrópicosunclassified